334 Whole Exome Sequencing of End Stage Renal Disease Associated Papillary Renal Cell Carcinoma (PRCCs). (11th January 2018) - Farooq, Taliya; Saeed, Faisal; Zhang, David; Huang, Weihua; Yin, Changhong; Zhong, Minghao
Abstract: Patients with end-stage renal disease (ESRD) have an increased risk of developing renal cell carcinoma (RCC). Whether ESRD-associated RCCs are genetically different from sporadic RCCs or there are any specific genetic alterations associated with papillary renal cell carcinoma (PRCC) arising in ESRD has never been studied. Therefore, we performed whole exome sequencing (WES) to comprehensively evaluate PRCC arising in ESRD for molecular changes. One of our surgical pathology databases was searched for PRCC arising in ESRD. Macrodissection was performed in some cases to ensure that at least 20% of the cells were neoplastic. Genomic DNA was extracted from formalin-fixed paraffin-embedded (FFPE) tissues by Qiagen AllPrep DNA/RNA Kit. The isolated genomic DNA was subject to targeted sequencing by using Illumina exome enrichment and sequencing kits. Using Illumina Variant Studio, we performed variant filtering, annotation, and interpretation with various sources of variant databases. And finally, we focused on the most frequently mutated genes associated with sporadic PRCCs described by TCGA (MET, SETD2, NF2, KDM6A, and SMARCB1). The WES-generated data with mean coverage >60x and 24, 000–33, 000 single nucleotide variants for each specimen. The six gene mutations found most frequently in sporadic PRCCs (MET, SETD2, NF2, KDM6A, and SMARCB1), were not identified in ESRD PRCCs. Interestingly, NCOR-1 mutations were found in all five ESRD-associated PRCCs. MAP3K1 and HLA-A were found in four out of five PRCCs. In addition, other frequent mutations were SH2B3 and ASXL1. Though there is a huge overlap of morphology and IHC profile level between ESRD-associated PRCCs and sporadic PRCCs, our study showed that ESRD-associated PRCCs carried genetic mutations distinct from those of sporadic PRCCs. NCOR-1 mutations were highly associated with ESRD-associated PRCCs and might be possible candidates for targeted therapy.